ARTIFICIAL INTELLIGENCE AS A CONTRIBUTION TO NEW EDUCATIONAL MARKETING STRATEGIES - Mora, César Arturo Carbache; Zambrano, Gema Viviana Carvajal; López, María Carmen Patiño (Seven Editora, 2025)
Artificial Intelligence (AI) has emerged as a strategic resource in educational marketing, allowing experiences to be personalized, behaviors to be predicted, and student recruitment and retention processes to be automated. This article analyzes the main applications, benefits, and challenges of AI in the marketing of educational institutions, proposing effective integration strategies based on an ethical and student-centered approach. The empirical results obtained through a survey applied to educational actors show a high acceptance of the use of AI in content personalization processes and improvement of student retention. In addition, international success stories are highlighted that show how the correct implementation of these technologies can generate substantial competitive advantages for higher education institutions. It is concluded that AI, more than a technological trend, represents a catalyst for strategic transformation in the educational field, as long as its application considers ethical principles, continuous training and a vision focused on the well-being of the student.DOI: https://doi.org/10.56238/sevened2025.018-027